2022
DOI: 10.1111/ppl.13654
|View full text |Cite
|
Sign up to set email alerts
|

Warming impacts on photosynthetic processes in dominant plant species in a subtropical forest

Abstract: Climate warming could shift some subtropical regions to a tropical climate in the next 30 years. Yet, climate warming impacts on subtropical species and ecosystems remain unclear. We conducted a passive warming experiment in a subtropical forest in Florida, USA, to determine warming impacts on four species differing in their climatic distribution, growth form, and functional type: Serenoa repens (palm), Andropogon glomeratus (C4 grass), Pinus palustris (needled evergreen tree), and Quercus laevis (broadleaved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 97 publications
(139 reference statements)
1
5
0
Order By: Relevance
“…A high temperature above the optimum can result in a decline in A area, as reported by a body of previous results and the present study (e.g., [ 14 , 42 , 58 ]; Tables 1 and 2 ). However, the function of PSII, using both F v ’/F m ’ and Φ PSII as the proxies [ 65 ], remained almost stable (e.g., [ 14 , 66 , 67 ]), and a slight promotion might even occur (Tables 1 and 2 ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…A high temperature above the optimum can result in a decline in A area, as reported by a body of previous results and the present study (e.g., [ 14 , 42 , 58 ]; Tables 1 and 2 ). However, the function of PSII, using both F v ’/F m ’ and Φ PSII as the proxies [ 65 ], remained almost stable (e.g., [ 14 , 66 , 67 ]), and a slight promotion might even occur (Tables 1 and 2 ).…”
Section: Discussionsupporting
confidence: 89%
“…C 4 plants often dominate warm environments and have been suggested to have a high resistance to high temperature relative to C 3 plants (e.g., [ 61 , 62 ]). Positive responses of C 4 species to warming have been observed in many studies (e.g., [ 58 , 61 ]). However, both C 3 and C 4 plants have been found to have similar photosynthetic responses to warming [ 63 , 64 ], and inhibition of C 4 plants may appear with a high temperature or a combination of warming and water deficit [ 42 , 58 ].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Plants growing on the limit of their distribution will likely suffer first from a change in climate, and the southern limit might become too hot and dry for the European oak. The article of Aspinwall et al (2022) in the current issue of Physiologia Plantarum, aims to investigate the effect of a rise in ambient temperature on four plant species, common and dominant in a subtropical forest (FL, USA). The authors found that two monocot species distributed in warmer climatic regions, a palm, and a grass, were able to handle the rise in temperature.…”
mentioning
confidence: 99%